Three-dimensional endosonography for staging of rectal cancer. - Hünerbein, M (1997)
OBJECTIVE: This prospective study was conducted to investigate the value of three-dimensional (3D) endosonography for staging of rectal cancer. SUMMARY BACKGROUND DATA: Transrectal ultrasound is the most sensitive technique for peroperative staging and follow-up of rectal cancer. Major limitations of this technique include the complexity of image interpretation and the inability to examine stenotic tumors or to identify recurrent rectal cancer. METHODS: Three-dimensional endosonography was performed in 100 patients with rectal tumors. Transrectal volume scans were obtained using a 3D multiplane transducer (7.5/10.0 MHz). Stenotic tumors were examined with a 3D frontfire transducer (5.0/7.5 MHz). The volume scans were processed and analyzed on a Combison 530 workstation (Kretztechnik, Zipf, Austria). RESULTS: The 3D endosonography and conventional endosonography were performed in 49 patients with nonstenotic rectal cancer. Display of volume data in three perpendicular planes or as 3D view facilitated the interpretation of ultrasound images and enhanced the diagnostic information of the data. The accuracy of 3D endosonography in the assessment of infiltration depth was 88% compared to 82% with the conventional technique. In the determination of lymph node involvement, 3D and two-dimensional endosonography provided accuracy rates of 79% and 74%, respectively. The 3D scanning allowed the visualization of obstructing tumors using reconstructed planes in front of the transducer. Correct assessment of the infiltration depth was possible in 15 of 21 patients with obstructing tumors (accuracy, 76%). Three-dimensional endosonography displayed suspicious pararectal lesions in 30 patients. Transrectal ultrasound-guided biopsy was extremely precise (accuracy, 98%) and showed malignancy in 10 of 30 patients. Histologic analysis changed the endosonographic diagnosis in 8 (27%) of the patients. CONCLUSIONS: The 3D endosonography permits examination of rectal cancer using previously unattainable planes and 3D views. The 3D imaging and ultrasound-guided biopsy seem capable to improve staging of rectal cancer and should be evaluated in further studies.